Economic analysis of paddy production among paddy farmers at Merlimau and Muar district / Fatin Nurr Fairuzz Amran, Fazleen Abd Fattah and Muhamad Zahid Muhamad - Amran, Fatin Nurr Fairuzz; Abd Fattah, Fazleen; Muhamad, Muhamad Zahid (Faculty of Plantation and Agrotechnology, 2018)
Rice is a nutritious staple food that contains starch (carbohydrates) which provide energy to people included Malaysian. Nowadays, the rice cultivation in Malaysia resulted high production cost and affects the profitability of fanners. The specific objectives were created to study the economic analysis of paddy production among paddy fanners. Economic analysis refers to the opportunity cost of resources employed. The main objectives of this study are to determine the economic cost and benefit among paddy farmers as well as to examine the factors affecting the profitability among paddy fanners. The factors that affect the profitability are subsidies, the role of information, distance of the mill from farm. availability of input, participation of organization and extension service. The primary data were used in this study where questionnaires were distributed to the target sample at two areas which are Merlimau, Melaka and Muar. Johor. This study included a target sample of 150 respondents of paddy fanners. The simple random sampling technique was used in this study. The data were analyzed using Cost Benefit Analysis (CBA) to examine the ratio of profitability both areas and used the Statistical Package for the Social Science (SPSS) for descriptive analysis and multiple regression analysis. The findings showed that farmers at Merlimau, Melaka has higher profitability than farmers at Muar. Johor were presented 2.5 and2.0 ratio. Multiple regression analysis was shown that distance of the mill from the farm and availability of input has significant relationship toward the profit of farmers. Government should take initiative actions such as provide information, training and improve technologies to help farmers to increase the profit.